Mechanical Properties of Stratified Hydrate-bearing Sediments. (May 2017) - Luo, Tingting; Liu, Weiguo; Li, Yanghui; Song, Yongchen; Wu, Qi; Wu, Zhaoran
Abstract: Methane hydrate–bearing layers will be disturbed during the production of methane hydrates, which may induce the deformation or settlement of the layers, and the destruction of engineering structures, so it's important to study the mechanical properties of the hydrate-bearing sediments. In this paper, specimens were prepared in which the methane hydrates were in different location of the specimens by a special deposition method in which the methane hydrate was put in the mold separating with the kaolin, the volume of methane hydrate was 40% of the whole volume of the specimen. A series of triaxial shear tests were carried out under different confining pressures of 1.25 MPa, 2.5 MPa, 3.75 MPa and 5 MPa, conditions with temperature of -6 o C and strain rate of 1%/min. The results indicated that the maximum deviator stress of the sediments increased with the declining of the clay of hydrate and the failure strength achieved maximum when the hydrate clay was in the center of the sediments; the failure strength increased with the increasing of the confining pressure in the low confining pressure stage.